The oxford handbook of english literature and theology - Hass, Andrew [ed.]; Jasper, David [ed.]; Jay, Elisabeth [ed.] (Oxford Oxford University Press, 2007)
The oxford handbook of english literature and theology is a defining volume of essays in which leading international scholars apply an interdisciplinary approach to the long and evolving relationship between english literature and theology. The volume first offers a chronological account of key moments in the formation of the tradition; goes on to demonstrate literary ways of reading the Bible, theological ways of reading literature, and literary conceptions of theological texts; and finally explores the great themes that have preoccupied the Jewish and Christian traditions. Framing editorial essays describe the history, the cultural implications, and the methodological issues of this now popular interdisciplinary study, before speculating as to its possible futures in a postmodern, multicultural world.
Keywords: Christian literature, English